The federal reserve's implicit inflation target and macroeconomic dynamics: A SVAR analysis - Haroon Mumtaz; Konstantinos Theodoridis (Cardiff University, Cardiff Business School, 2018)
This paper identifies shocks to the Federal Reserve\~Os inflation target as VAR innovations that make the largest contribution to future movements in long-horizon inflation expectations. The effectiveness of this scheme is documented via Monte-Carlo experiments. The estimated impulse responses indicate that a positive shock to the target is associated with a large increase in inàation and long-term interest rates in the US and the industrialised world. Target shocks are estimated to be a vital factor behind the increase in inflation during the pre-1980 period and are an important driver of the decline in long-term interest rates over the last two decades.
Keywords: C5; E1; E5; E6; 330; SVAR; DSGE model; inflation target; International transmission